Perceptions and Referral Trends into Phase I Oncology Trials: Results of a Clinical Survey. (27th June 2011) - Brunetto, Andre; Olmos, David; Arkenau, Hendrik-Tobias; Tan, Daniel; Yap, Timomy; de Bono, Johann; Barriuso, Jorge; Kaye, Stan
Abstract : Introduction . A survey was sent to referring oncologists (ROs) to explore the reasons behind their referral patterns and perceptions of Phase I studies before and after being provided with outcome data from advanced colorectal cancer (ACRC) patients who participated in Phase I trials at the Royal Marsden Hospital (RMH). Results . The response rate was 32/50 (64%). The most common reason for referral was exhaustion of standard treatments (31%), and the main reason for referring to the RMH was proximity to patients (28%). The most frequent clinical parameter assessed prior to referral was performance status (93%). ROs spent a median of 15 min (range: 5–45 min) discussing general aspects of Phase I trials. In the second part of the questionnaire, after reviewing clinical outcome data of ACRC patients who participated in Phase I trials, 47% would change their approach, specifically, spend more time to discuss risks and benefits of Phase I trials (9%), consider prognostic factors before referral (13%), and increase the number of referrals (25%). Conclusion . This is the first report focusing on communication between ROs and a specialist Phase I unit. Outcome reporting can improve communication with ROs and importantly has the potential for better patient selection considered for Phase I oncology trials.